The Effect of the Windah Basudara Youtube Channel on Fulfilling Game Information Needs - Kristiantoro , Julian; Nuraeni, Reni (ARRUS Journal of Social Sciences and Humanities, 2023)
Social media is currently widely used by internet users in Indonesia as a means to find information needs. The social media platform that is most in demand by the public today is Youtube. Youtube provides various types of content that are presented independently by content creators or referred to as YouTubers. One of the content on Youtube is entertainment content in the form of game content. Apart from being entertainment content, game content can also make many Youtube users obtain information about games. Currently, there are many Youtubers who create this content, one of the big Youtuber names that is well known to the public is Windah Basudara. This study aims to determine whether Windah Basudara's Youtube channel has an effect on fulfilling game information needs. The research method used in this research is quantitative descriptive, the sample used is Youtube subscribers Windah Basudara as many as 100 respondents by carrying out a normality test, simple linear regression analysis, correlation coefficient test, coefficient of determination test, and hypothesis testing. This study found that Windah Basudara's Youtube channel variable has a positive and significant influence on fulfilling game information needs. The Windah Basudara Youtube Channel has an influence on fulfilling the game information needs of its subscribers with a percentage of 78.7%, and the remaining 21.3% is influenced by other factors not examined in this study.